Optimizing Air Traffic Management in Europe by the introduction of the Single European Sky - González, Rocío Jáuregui (Cognitive Sustainability, 2024)
Europe´s airspace is facing an arduous situation due to its congestion, which leads to multiple delays and inefficient flights. Introducing the Single European Sky Air Traffic Management (SESAR) initiative will conquer a transformative shift in Europe´s Air Traffic Management (ATM), achieving more optimised and sustainable routes throughout the continent. Therefore, through the successful implementation of the SESAR initiative, we will enhance the performance of Europe´s ATMs in capacity, safety, efficiency, and sustainability. This paper evaluates Europe´s current airspace and highlights the positive impacts of the initiative in the different areas of improvement. Utilising current data provided by the airlines, qualitative methods are applied to prove the effect that SESAR will achieve on different routes. The research results demonstrate how introducing the SESAR will reduce flight distance, fuel consumption, and emissions. In conclusion, this research emphasises the significance of implementing the SESAR to update air traffic control throughout Europe. The aviation industry is experiencing a modernisation that is expected to result in lower operating costs, fewer delays, and a reduction in the environmental impact of their flights.